Fuzzy hysteresis current control of five phase permanent magnet motor under open-circuit faults - Fatiha, Mekri; El Fadhel Loubaba Bekri, Oum (International Journal of Engineering and Technology, 2018)
This paper presents a new current controller of a PWM of multiphase PM machines with a fuzzy logic band. With this kind of system it is possible to determine optimal currents references which maximize the torque density of the system when one or two phases are open circuited. We propose in this paper to combine this optimal reference current generation with fuzzy hysteresis control band. This solution allows a good tracking of these unconventional reference currents with a fixed switching frequency for the VSI. The study carried on simulation via software MatLab/Simulink.Â Â